An Experimental Analysis of Precipitated Silica in Petroleum-Contaminated Clay for the Strengthening of Soil Characteristics - Ponnusamy Kulanthaivel (17789018) (2023)
In recent times, the environmental impacts of petroleum-contaminated clay (PC clay) have intensified, leading to more severe detrimental effects. To address this issue, the use of precipitated silica (P silica) has proven to be an effective solution. P silica offers improved treatment for the contaminated clay and enhances the engineering properties of the soil. A series of experiments such as pH test, electrical conductivity test, unconfined compressive strength (UCS) test, California bearing ratio (CBR) test, free swell index (FSI) test, compaction test and Atterberg limit tests were conducted to compare the soil characteristics of the PC clay with and without the treatment of P silica. The PC clay soil specimens were tested after the inclusion of P silica with varying dosages of 0%, 3%, 6%, 9% and 12% by dry weight of clay soil. The inclusion of P silica at a dosage of 6% resulted in the optimum strength of 275.12 kPa. This dosage also led to a reduction in free swell index (FSI) and maximum dry density (MDD), indicating a flocculation mechanism caused by the presence of P silica. Additionally, there was an improvement in stiffness and strength parameters, as evidenced by the enhancement in CBR (California bearing ratio). Therefore, the effective utilization of P silica in contaminated clay soil provides a variety of applications in the geotechnical field. Other Information Published in: Iranian Journal of Science and Technology, Transactions of Civil Engineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s40996-023-01242-3